A= h(b+c) solve for b

Answers

Answer 1
Answer: A=h(b+c)
A/h=b+c
b=(A/h)-c

Answer: b=(A/h)-c
Answer 2
Answer: (a/h)-c=b that is the answer. remember PEMDAS

Related Questions

it takes a hose 4 minutes to fill a rectangle 9inc long, 11inches wide and 12 inches tall, how long will it take to fill an aquarium 24 by 25 by 33 inches tall
A bag contains blue and yellow marbles. Two marbles are drawn without replacement. The probability of selecting a blue marble and then a yellow marble is 0.37, and the probability of selecting a blue marble on the first draw is 0.55. What is the probability of selecting a yellow marble on the second draw, if the first marble drawn was blue? A) 18% B) 20% C) 46% D) 67%
Does the graph represent an exponential growthor an exponential decay function?
A jar lid has a diameter of 42 millimeters.What is the circumference of the lid?
The function f(t) = 349.2(0.98)t models the relationship between t, the time an oven spends cooling and the temperature of the oven. For which temperature will the model most accurately predict the time spent cooling? 0 100 300 400

Solve the following system of equations.-2x + y = 1
-4x + y = -1

A) (3,1)
B) (-1,3)
C) (-1,-3)
D) (1,3)

Answers

Hi Brainiac


-2x+y=1

-4x+y=-1


We need to solve -2x+y=1 for y

Now let's start by adding 2x to both sides

-2x+y+2x=1+2xy=2x+1

Substitute 2x+1 for y in -4x+y=-1

-4x+y=-1

-4x+2x+1=-1

-2x+1=-1

Add -1 to both sides

-2x+1-1=-1-1

-2x=-2

Now divide both sides by -2 so we can fine the value for x

-2x/-2= -2/-2

x=1

The last step is to substitute 1 for x in y=2x+1

y=2x+1

y=(2)(1)+1

y= 2+1

y= 3


Answer : D , (1,3)


Good night :)

What is the solution of the equation? 3 = b + 3
a. 1
b. 6
c. 9
d. 0

Answers

If you would like to know what is the solution of the equation 3 = b + 3, you can calculate this using the following steps:

3 = b + 3
b = 3 - 3
b = 0

The correct result would be d. 0.
3 = b + 3

Subtract 3 on both sides.

3 = b + 3\n3-3= b+3-3\n3-3 = b\n\n0 = b\n\n\n\boxed{\bf{b=0}}

Your final answer is d. 0.

Solve 2x²-3x-7=0 using completing the square method​

Answers

Answer:

Use the formula ( b 2 ) 2 in order to create a new term.

Solve for x by using this term to complete the square.

Exact Form: x = ± √ 65 4 + 3 4

Decimal Form: x = 2.76556443 … , − 1.26556443 …

The equation x2 + y2 − 2x + 2y − 1 = 0 is the general form of the equation of a circle. What is the standard form of the equation?

Answers

Answer:

(x-1)^2+ (y+1)^2=3

Step-by-step explanation:

x^2 + y^2 - 2x + 2y - 1 = 0

Standard form of the equation is (x-h)^2 + (y-k)^2= r^2

To get standard form we apply completing the square method

x^2-2x+ y^2+ 2y - 1 = 0

Take coefficient of x  and y . Divide it by 2 and then square it

(2)/(2) =1 and 1^2=1

Add and subtract 1

(x^2-2x)+(y^2+ 2y) - 1 = 0

(x^2-2x+1-1)+(y^2+ 2y+1-1) - 1 = 0

(x^2-2x+1)+(y^2+ 2y+1)-1-1- 1 = 0

(x^2-2x+1)+(y^2+ 2y+1)-3= 0

Now write the parenthesis in square form

(x-1)(x-1)+ (y+1)(y+1)-3= 0

(x-1)^2+ (y+1)^2-3= 0 , add 3 on both sides

(x-1)^2+ (y+1)^2=3 is the standard form

x^2 + y^2 - 2x + 2y - 1 = 0

(x^2 - 2x) + (y^2 + 2y) - 1 = 0

(x^2 - 2x + 1) + (y^2 + 2y + 1) - 1 - 1 - 1 = 0

(x - 1)^2 + (y + 1)^2 - 3 = 0

(x - 1)^2 + (y + 1)^2 = 3


Simplify the expressions (x-2) (3x-4)

Answers

This expression can be simplified using the FOIL method of multiplication (first, outer, inner, last).

First: x · 3x = 3x²
Outer: x · -4 = -4x
Inner: -2 · 3x = -6x
Last: -2 · -4 = 8

Combine all these terms, and it leaves you with your final answer:
3x² - 10x + 8

An arc on a circle measures 85°. The measure of the central angle, in radians, is within which range?0 to radians to π radiansπ to radians to π radians

Answers

The measure of the central angle is within 0 to π radians.

Equation

An equation is an expression that shows the relationship between two or more variables and numbers.

Angle in radian = angle in degrees * π / 180

Given that the angle = 85°, hence:

Angle in radian = 85 * (π/180) = 0.472π rad

The measure of the central angle is within 0 to π radians.

Find out more on Equation at: brainly.com/question/13763238

Answer:

the answer to this is A

Step-by-step explanation: